Satisfaction, water and fertilizer use in the American residential macrosystem. (29th February 2016) - Groffman, Peter M; Grove, J Morgan; Polsky, Colin; Bettez, Neil D; Morse, Jennifer L; Cavender-Bares, Jeannine; Hall, Sharon J; Heffernan, James B; Hobbie, Sarah E; Larson, Kelli L; Neill, Christopher; Nelson, Kristen; et al.
Abstract: Residential yards across the US look remarkably similar despite marked variation in climate and soil, yet the drivers of this homogenization are unknown. Telephone surveys of fertilizer and irrigation use and satisfaction with the natural environment, and measurements of inherent water and nitrogen availability in six US cities (Boston, Baltimore, Miami, Minneapolis-St. Paul, Phoenix, Los Angeles) showed that the percentage of people using irrigation at least once in a year was relatively invariant with little difference between the wettest (Miami, 85%) and driest (Phoenix, 89%) cities. The percentage of people using fertilizer at least once in a year also ranged narrowly (52%–71%), while soil nitrogen supply varied by 10x. Residents expressed similar levels of satisfaction with the natural environment in their neighborhoods. The nature and extent of this satisfaction must be understood if environmental managers hope to effect change in the establishment and maintenance of residential ecosystems.